Subretinal Injection of HY Peptides Induces Systemic Antigen-Specific Inhibition of Effector CD4+ and CD8+ T-Cell Responses - Vendomèle, Julie; Dehmani, Safa; Khebizi, Quentin; Galy, Anne; Fisson, Sylvain (Frontiers in Immunology, 2018)
Purpose: Injection of an antigen into the anterior chamber of the eye induces a peripheral antigen-specific immune modulation mechanism, known as anterior chamber-associated immune deviation (ACAID). Delayed-type hypersensitivity experiments argue that the subretinal space of the eye displays properties similar to ACAID. However, no investigation was performed regarding the differential impact of a subretinal antigen injection on peripheral CD4+ versus CD8+ T-cells, on the potential immune deviation regarding Th profiles, and on the antigen-specificity of the inhibition. A better understanding of these mechanisms is crucial to improve safety and immunomonitoring of ongoing therapeutic approaches targeting the subretinal space. The aim of this study is to characterize the proliferative capacities and cytokine patterns of antigen-specific CD4+ and CD8+ T cells after a subretinal injection of antigen in mice. Methods: UTY and DBY peptides which respectively include MHCI- and MHCII-restricted T cell epitopes of the mouse HY male antigen, were injected into the subretinal space of C57BL/6 female mice. Two weeks later, these mice were immunized subcutaneously with these peptides and compared to control mice. A week later, T-cell immune responses were analyzed by IFNγ ELISpot assays and cytokine measurements (IL-2, IL-4, IL-6, IL-10, IL-13, IL-17a, IFNγ, TNFα, GM-CSF, and MCP-1) in the spleen and with proliferation assays in draining lymph nodes. Results: Immune cells from mice that received HY peptides in the subretinal space before immunization, compared with those from control immunized mice, secreted significantly smaller quantities of Th1/Tc1, Th2/Tc2 and Th17/Tc17 cytokines, and HY-specific CD4+ T cells proliferated less in response to HY peptides. Conclusion: Taken together, our data clearly demonstrate that the subretinal injection of HY peptides induces a systemic HY-specific inhibition of conventional Th profiles and CD8+ T cells. We propose to call this phenomenon SRAII, for subretinal-associated immune inhibition.